Revisiting the demeanour effect: a video-observational analysis of encounters between law enforcement officers and citizens in Amsterdam - Sunde, Hans Myhre (Policing and society, 2023)
We investigate the ‘demeanour hypothesis’, stating that police officers are more likely to arrest and use force against citizens who display a ‘bad attitude’. We observed 78 encounters captured on surveillance cameras in the city of Amsterdam. Video material allowed us to code specific behaviours (‘citizen pointed at officer’) instead of the more ambiguous interpretation of behaviour (‘citizen was disrespectful’) used in prior studies. We employ two regression analyses to estimate the extent to which different types of citizens’ behaviour – ‘bad attitude’, non-compliance, and aggression and crime – relate to physical coercive behaviour by law enforcement agents. After controlling for non-compliant, aggressive and criminal behaviours, as well as situational and individual features, citizens’ ‘bad attitude’ behaviours remain associated with physical coercion. However, our data also shows that the effects of aggressive and criminal behaviours are far stronger than that of ‘bad attitude’ behaviours. Yet, there is an observable ‘demeanour effect’ in our sample. Conceptually, we provide a more thorough behavioural description of what a ‘bad attitude’ looks like. Practically, our findings can be used in training, such as scenario or VR training, in order to raise officers’ awareness of citizens’ behaviours, and may assist them to prevent escalation in their encounters with the public.